المناخ التنظيمي بالمدرسة الجزائرية بين الواقع والمأمول - بوبيدي, لامية; عطا الله, محمد (University of Eloued جامعة الوادي, 2020)
تؤدي المدرسة بمختلف أطوارها دورا هاما في تحقيق التنمية والرقي المجتمعي، وذلك مرجعه كونها تولي اهتماما بالمورد البشري في محاولة نحو الاستثمار فيه وجعله مستقبلا رأسمال فاعل في المشروع الحضاري. يعتمد نجاح المؤسسات التربوية في تحقيق أهدافها، على عدد من المتغيرات ويعد المناخ التنظيمي أحد أهم هذه المتغيرات، والتي يرتبط درجة نجاحها وتحقيق أهدافها بما تتوفر عليه هذه المؤسسة من محفزات ومعززات للأداء الجيد والفعال لدى الفاعلين بها. جاءت هذه الورقة البحثية عبارة عن دراسة سوسيوتربوية نحاول من خلالها القاء الضوء على راهن المدرسة الجزائرية في ظل ما تتوفر عليه من مناخ وظيفي وتنظيمي قد يسهم في جعلها بيئة دافعة نحو العطاء او ان تصبح بيئة تعمها الصراعات والمشكلات. Abstract The school, in its various phases, plays an important role in achieving social development, due to the fact that it pays attention to the human resource in an attempt to invest in it and make it a future active capital in the civilized project. The success of educational institutions in achieving their goals depends on a number of variables. The organizational climate is one of the most important of these variables, and the degree of its success and achievement of its goals is related to the incentives and enhancements this institution has for the good and effective performance of its actors. This research paper is a socio-educational study through which we try to shed light on the current school of Algeria in light of the available job and organizational climate that may contribute to making it a driving environment towards giving or becoming an environment full of conflicts and problems.
The organizational climate in the Algerian school - between reality and expectations
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: المناخ التنظيمي –المدرسة الجزائرية; Organizational climate - Algerian school